ISSUES OF IMPROVING THE ECONOMY OF BUILDING MATERIAL - WOOD PRODUCTION - Abobakirova Zebuniso Asrorovna; Umarov Shodiljon Abdug ‘ofurovich; Mirzayeva Zarnigor Alisher qizi; Solijonov Foziljon Sodiqjon o‘g‘li (Journals Park Publishing, 2022)
This article is devoted to improving the construction economy by increasing the strength of wood growing in the conditions of Central Asia and their large – scale use in the construction production industry.
Keywords: building material industry, wood production, modification, local Poplar.